GENETIC RESISTANCE OF AWASSI SHEEP INFECTED WTH HAEMONCIIUS CONTORTUS ; A. THE EFFECT OF NUTRITION LEVEL ON PRODUCTION TRAITS . - Abid Al-Jabber , L.; Al-Zuhairi, M.; A. Ali, D. (The Iraqi Journal of Veterinary Medicine, 1992)
Twenty Awassi sheep were divided to two groups , the first fed on high level of nutrition and the other fed low level of nutrition . Each group was divided to two groups , the first infected with 500 larvae/Kg body weight of Haemonchus contortus and the second was used as a control . Weight gain , wool production , feed conversion efficiency and egg/G.. were recorded weekly for 13 weeks post infection .All production Traits of low level nutrition group were more effected than high level nutrition group , and these results revealed highly significant (P<0.001) effect of nutrition level on genetic resistance . There were significant (P<0.05) effect of nutrition treatment interaction on E.P.G. weight gain , feed conversion efficiency but not significant on wool production .